Giant quadratic magneto-optical Kerr effect in (Eu, Gd)O films for magnetic field sensing. (June 2020) - Kats, Vladimir N.; Nefedov, Sergey G.; Shelukhin, Leonid A.; Usachev, Pavel A.; Averyanov, Dmitry V.; Karateev, Igor A.; Parfenov, Oleg E.; Taldenkov, Alexander N.; Tokmachev, Andrey M.; Storchak, Vyacheslav G.; Pavlov, Victor V.
Highlights: Epitaxial films of ferromagnetic (Eu, Gd)O on yttria-stabilized zirconia substrate of perfect structural quality. Quadratic magneto-optical Kerr effect (QMOKE) of a record-high amplitude in (Eu, Gd)O films. High sensitivity of the giant QMOKE to the in-plane magnetic anisotropy for new-type tangential magnetic field sensors. Graphical abstract: Abstract: A quadratic magneto-optical Kerr effect (QMOKE) of exceptionally high value, strong polar and longitudinal linear Kerr effects have been demonstrated in thin films of ferromagnetic (Eu, Gd)O and the parent compound EuO epitaxially grown on yttria-stabilized zirconia. At a photon energy of 1.85 eV, the effect reaches 1 deg in Eu0.97 Gd0.03 O exceeding the reported values of giant QMOKE by an order of magnitude. It is demonstrated that the QMOKE in (Eu, Gd)O enables detailed optical studies of the in-plane magnetic anisotropy of the film. The observed giant QMOKE may be employed for the development of vectorial sensors of weak magnetic fields.